1999
DOI: 10.1080/009841099157674
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Antinuclear Antibodies in a Rural Population

Abstract: Exposure to environmentally and occupationally encountered toxicants can be associated with the development of certain autoimmune diseases and with the induction of antinuclear antibodies (ANA). Some chemicals used in the agricultural industry are known to affect immune function but their roles in the induction of autoimmunity in general, and ANA in particular, have not been reported previously. This study was undertaken to establish the prevalence of ANA in a rural population and to determine environmental an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…It was reported that this rate could reach to 15% in further ages. 12 - 14 Tan et al 12 detected ANA positivity rate as 31.7% in healthy individuals using a dilution of 1:40 of the sera. It is suggested that test should be repeated in a patient that were positive for ANA after a 3-6 months period when the symptoms of the disease disappear.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that this rate could reach to 15% in further ages. 12 - 14 Tan et al 12 detected ANA positivity rate as 31.7% in healthy individuals using a dilution of 1:40 of the sera. It is suggested that test should be repeated in a patient that were positive for ANA after a 3-6 months period when the symptoms of the disease disappear.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the association between pesticides and RA have been inconsistent. Several epidemiologic studies have reported increased RA or increased prevalence of antinuclear antibody among farmers (Lundberg et al 1994; Olsson et al 2004; Rosenberg et al 1999), but others did not (De Roos et al 2005). Interpretation of previous studies may be limited because the exposure assessment was based on questionnaires about exposure to pesticides rather than on direct measurement of pesticide concentrations in blood.…”
Section: Discussionmentioning
confidence: 99%
“…Insecticide exposure was associated with low-titer ANA positivity in a cross-sectional study of 322 rural residents in Saskatchewan, Canada (29), whereas there was no significant association with other classes of pesticides, including herbicides and fungicides. Specifically, only pyrethroid insecticides and oilseed production were associated ANA positivity in a multivariate model including various pesticides and crops.…”
Section: Exposuresmentioning
confidence: 99%